Women’s employment in agri-food systems - Slavchevska, Vanya (Food and Agriculture Organization of the United Nations, 2023)
Agri-food systems (AFS) are an important livelihood source for women, particularly in low- and middleincome countries. However, to the best of our knowledge, no formal statistics or other available data readily identify and quantify the number of women and men whose livelihood depends on AFS globally. There is also limited information on the quality of their employment in AFS. To bridge this gap, we expand Davis’s 2023 methodology and produce new global and regional estimates for people working in AFS disaggregated by sex. Our findings reveal that, in 2019, 36% of working women and 38% of working men were employed in AFS, globally. This reflects a decline of about 10 percentage points for women and 3 percentage points for men since 2005, mainly driven by a decline of employment in agriculture. We further find that during the first year of the COVID-19 pandemic, women lost jobs at greater rates than men, particularly in the off-farm segment of AFS. Finally, we use diverse data sources to analyze the type of employment in AFS and we find that women are more likely than men to be employed in vulnerable forms of employment, to be part-time, and in the less likely to be working in the more lucrative segments of AFS like transportation and wholesale trading.